Launching a Permanent Out-of-Hour Interventional Radiology Service: Single-Center Experience from a German University Hospital - Goltz, J. P.; Janssen, H.; Petritsch, B.; Kickuth, R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To evaluate the feasibility, frequency of use, types of intervention and labor costs of a formal round-the-clock interventional radiology on-call service.Materials and Methods: In 11/2011 a formal and permanent out-of-hour interventional radiology rota in addition to the general radiology out-of-hour rota (OOHR) was established. We retrospectively screened the interventional radiology database for procedures completed outside regular working hours, reviewed all interventions and manually selected cases in which the on-call interventionist was called in from home. We determined the type, frequency of use and costs (€/year and procedure) of this service between 1/2012 and 12/2012. The referring physicians’ (sub-) specialties were evaluated.Results: During the 12-month period, the on-call interventionists (n = 3) performed 92 procedures OOH. The procedures included angiography and hemorrhage control (n = 36, 39.1 %), angiography and intervention for acute limb ischemia (n = 25, 27.2 %), percutaneous biliary drainage (PTCD) (n = 10, 10.9 %), angiography for non-occlusive ischemia (n = 7, 7.6 %), and other (n = 14, 15.3 %). The total labor costs for the OOHR were € 42,312.21 (€ 32,982.60 lump sum for stand-by, €  9,329.61 for hours spent on procedures). The labor costs per procedure totaled € 459.92. The referring physicians’ specialties were general/visceral (n = 25), vascular surgery (n = 24), internal medicine (n = 21), cardiac/thoracic vascular (n = 9), trauma surgery (n = 5), urology (n = 5), and anesthesiology (n = 3).Conclusion: A formal interventional OOHR is practicable in a university hospital setting. Most procedures were requested by general, vascular, and thoracic surgery as well as internal medicine with a focus on hemorrhage control, treatment of acute limb ischemia, and PTCD. The overall labor costs for the OOHR appear moderate.Key points:• In a university setting an OOHR for IR is feasible.• Labor costs per procedure appear moderate.• Hemorrhage control and treatment of limb ischemia were the most frequent procedures.Citation Format:• Goltz JP, Janssen H, Petritsch B et al. Launching a Permanent Out-of-Hour Interventional Radiology Service: Single-Center Experience from a German University Hospital. Fortschr Röntgenstr 2014; 186: 136 – 141
Keywords: interventional procedures; cost-effectiveness; out-of-hour rota; radiology workload; emergency radiology